On Theory of Recognition - Hameed, Rana Yousuf; Al-Jabery, Salah Fulifel Ayyed (Al-Adab Journal, 2022)
There is more than one meaning to recognition. What is new is that Hegel considers interpersonal relationships, not as moral relationships in the first place, and considers mutual recognition as more than a moral requirement. As for Honth, he is closer to Paul Ricoeur's position that the term recognition is a category of multiple meanings and connotations, and all this semantic plurality can be traced back to three meanings: identification, self-recognition, and mutual recognition. The Recognition carries a moral meaning, and expresses an abstract and ethical understanding of behavior and human relations, and is dominated by normative content that has nothing to do with the dynamics of reality, subjective relations, or the path of society, and that recognition along with trust represent the most important foundations of modern thought and modern view of man, work and creativity, on the horizon of symbolic capital and social. Recognition in language means acknowledgment of a great service rendered to us by an individual or a group, or the need to show appreciation towards the other. Therefore, recognition is an essential issue for a person, as its absence negatively a(ects the achievement of self-confidence and appreciation from others. Its absence makes the individual at risk of losing his personality; and then feeling a kind of contempt, humiliation, anger and indignation; Therefore, recognition is of vital importance: first from the psychological point of view, considering that the psyche of the individual continues to sufer from new characteristics instead of the conditions for the possibility of its self-actualization; secondly, from the social existential point of view; The absence of recognition leads to the impoverishment of groups or society of the social infrastructure that forms the basis for social ties and the promotion of coexistence.